2010
DOI: 10.1038/ja.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antilarval compounds from marine gorgonian-associated bacterium Bacillus amyloliquefaciens SCSIO 00856

Abstract: It is well understood that corals harbor diverse microbial communities. Recently, many coral-associated bacteria have been characterized as sources of marine natural products, especially as the coral surface is more nutrient rich than seawater or even sediments. 1,2 Colonization of coral surfaces by bacteria and other microorganisms is mostly nondestructive to corals. Owing to the close spatial vicinity of these biofilm-forming bacteria, it can be expected that the indigenous microbial population is adapted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Macrolactins V ( 86 ) and S ( 69 ) (Figure 17 and Figure 21) were isolated from the culture broth of a marine bacterium, B. amyloliquefaciens SCSIO 00856, which was isolated from a South China Sea gorgonian, Junceella juncea [48]. Macrolactin V ( 86 ) exhibited potent antibacterial activity against E. coli , B. subtilis and S. aureus with an MIC value of 0.1 µg/mL, and no activity against B. thuringiensis .…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrolactins V ( 86 ) and S ( 69 ) (Figure 17 and Figure 21) were isolated from the culture broth of a marine bacterium, B. amyloliquefaciens SCSIO 00856, which was isolated from a South China Sea gorgonian, Junceella juncea [48]. Macrolactin V ( 86 ) exhibited potent antibacterial activity against E. coli , B. subtilis and S. aureus with an MIC value of 0.1 µg/mL, and no activity against B. thuringiensis .…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Macrolactin V ( 86 ) exhibited potent antibacterial activity against E. coli , B. subtilis and S. aureus with an MIC value of 0.1 µg/mL, and no activity against B. thuringiensis . Macrolactin S ( 69 ) showed strong antibacterial activity against both E. coli and S. aureus with MIC values of 0.3 and 0.1 µg/mL, respectively, but weak activity against B. subtilis (MIC 100 µg/mL), which indicated that the configuration of 7-OH may affect the antibacterial activity of the epimers 86 and 69 [48]. …”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Therefore, they are excellent candidates for the search of symbiotic bacteria with antimicrobial potential. Cnidarians, as soft corals, gorgonians and sea anemones, have a high diversity of symbiotic bacteria [ 27 , 28 ], especially as the coral surface is more nutrient-rich than seawater or sediments [ 29 , 30 ]. Indeed, some authors have detected coral-associated bacteria as sources of antimicrobial products [ 27 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structures most closely related to atacamycins and chaxalactins are the 24-membered polyketides of the macrolactin family. To date, macrolactins A-V have been isolated from marine and soil bacterial isolates and have been shown to possess antibacterial, antilarval, antiviral, and antitumor activities (Gao et al 2010). …”
Section: Macrolactonesmentioning
confidence: 99%